2013
DOI: 10.1515/cclm-2013-0535
|View full text |Cite
|
Sign up to set email alerts
|

Androgen deprivation decreases prostate specific antigen in the absence of tumor: implications for interpretation of PSA results

Abstract: Background: Prostate-specific antigen (PSA) is used as an outcome measure for relapsed disease in prostate cancer. Nonetheless, there are considerable concerns about its indiscriminate use as a surrogate endpoint for cell growth or survival. We hypothesized that treatment with a luteinizing hormone releasing hormone (LHRH) analog would decrease PSA levels even in the absence of malignant disease. Methods: We determined testosterone and PSA levels in 30 healthy volunteers after a single intramuscular injection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Combined androgen blockade reduced PSA values in most patients by more than 80% in the first month [ 13 ]. However, some studies had shown that PSA decline did not indicate tumor cell death, but instead represented AR pathway inhibition and subsequent reduced PSA secretion [ 14 ]. However, a slower PSA reduction following an initial rapid decline is considered representative of tumor load reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Combined androgen blockade reduced PSA values in most patients by more than 80% in the first month [ 13 ]. However, some studies had shown that PSA decline did not indicate tumor cell death, but instead represented AR pathway inhibition and subsequent reduced PSA secretion [ 14 ]. However, a slower PSA reduction following an initial rapid decline is considered representative of tumor load reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence reveals that AR is critically involved in PC progression (Pelekanou & Castanas, 2016; Zarif & Miranti, 2016) and metastasis (Yin et al, 2014), while ADT using luteinizing hormone releasing hormone agonist decreases PSA level by testosterone deprivation (Liu et al, 2017; Wenisch et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In the setting of nmCRPC, when no disease is detectable by conventional imaging tests, PSA testing indirectly monitors tumour AR signalling activity, which can correlate with disease burden. However, it must be noted that PSA declines are not proven surrogate biomarkers of survival outcome and that downregulation of AR signalling does not always represent tumour cell elimination, and indeed it is well recognised that some aggressive prostate cancers are low PSA secretors [25,26]. In the nmCRPC state, more data are needed to demonstrate that slowing of PSA velocity, or achievement of a greater PSA decline in the nmCRPC state, is associated with meaningful benefit in terms of extending survival or improving quality of life.…”
Section: Other Trials Evaluating Ar Signalling Targeting Agents In Nmcrpcmentioning
confidence: 99%